PERAN PERBANKAN SYARIAH DALAM PENYERAPAN TENAGA KERJA PADA SEKTOR RIIL - Moch. Edman Syarief; Setiawan Setiawan; Nabila Nur Khairina (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
This paper aims to examine the labor absorption in the real sector, including three essential determinants, namely Non-Performing Financing, Third Party Funds, and Profit-Sharing Financing. The object of this research is the Islamic Commercial Bank in Indonesia. Data analysis techniques in this study use path analysis. The results showed that (i) Profit Sharing Financing and Non-Performing Financing directly had a positive and significant effect on the Real Sector Labor Absorption variable; (ii) Third Party Funds are insignificant to the variable Real Sector Labor Absorption; (iv) Third Party Funds have a positive and significant effect on the variable Real Sector Labor Absorption through Profit-Sharing Financing; and (v) Non-Performing Financing is not significant to the Real Sector Labor Absorption variable through Profit-Sharing Financing.